Resistance of Grapevine Rootstocks to Meloidogyne incognita under Field Conditions - Loubser, J .T.; Meyer, A.J. (South African Journal of Enology and Viticulture, 2017)
Resistance of grapevine rootstocks to root-knot nematodes (Meloidogyne incognita) was studied in field trials. Resistance was found to be adequately expressed by the degree of galling. A highly significant positive correlation exists between nematode populations in the soil as well as nematode reproduction and galling, while grapevine growth and yield were negatively related to the degree of infestation. However, information regarding rootstock tolerance and intolerance (sensitivity) was not considered reliable. It was further shown that a susceptible scion would not lower the resistance of the rootstock involved. Based on their rate of galling, rootstocks Ramsey, 99 Richter PS, Dogridge, Freedom, Harmony and 101-14 Mgt are resistant while Jacquez, 140 Ruggeri, Grezot-1, Maleque 44-53 and Constantia Metallica are susceptible.